Matrimonio y vida cotidiana en el graven central costarricense (1851 - 1890) - Cerdas Bokhan, Dorita (Revista de historia., 1992)
This article is based on sources from the archives of the Catholic Church. It focuses on the doctrine of the Catholic Church regarding marriage, and on actual marital relations in the central graven of Costa Rica, during the second half of the nineteenth century, It also includes a discussion of the roles assigned to husband and wife, as well as the main deviant behaviours: extreme cruelty, adultery and problems caused by alcoholism.